Flourishing of arts, culture, literature and history during the Mughal Era (1526-1857) - Arshad Islam, Islam (2018)
The Indian Subcontinent has contained a vast array of innumerable ethnicities, cultures, traditions and languages since the dawn of human civilization. It is a land of immense diversity including a variety of races and religions. It has always remained a dynamic and complex entity within and against which varied peoples and interests interacted. India’s multicultural influences are universally evident, in food, clothes, and places. Mughal rule marked a significant turning point, reinvigorating the arts, science and culture with extensive and lavish patronage and support. The Mughals were responsible for the development of a variety of languages, wonderful world-famous monuments, paintings, and miniature paintings, landscaping, gardening, building caravansaries exhibiting their fine imaginative taste throughout the empire. This article charts the origin and growth of arts, culture, literature and history in the Indian Subcontinent.